What can changes in structural factors tell us about unemployment in Europe? - Julian Morgan; Annabelle Mourougane (European Central Bank (ECB), 2001)
This paper examines the impact of temporal variation in labour market institutions and other structural factors on unemployment in Europe. These include the influence of trade unions, social security benefits, employment security, mismatch between job seekers and vacancies, the minimum wage and factors which drive a wedge between consumer and producer prices. With this aim, a system including a labour demand and a wage equation is estimated in pooled time-series data for the six largest EU countries for the 1980s and 1990s, allowing for country-specific fixed-effects, institutional effects and adjustment terms. Our estimates suggest that changes in regional mismatch, trade union density and the ratio between consumer and producer prices are positively associated with structural unemployment. This result is robust to a wide variety of different specifications of the model, including a larger sample of eight EU countries. No consistent role is found for the other institutional factors.
Keywords: E24; J30; C33; 330; Labour market institutions; panel estimation; structural unemployment